Investigation of preventive behaviors in the beginning term of Covid/19 pandemic, evidence from Turkey - Ekinci, Gülay; Çınar, Fadime; Çapar, Haşim; Ekinci, Gülay (Dilaver Tengilimoğlu, 2022)
Aim: In this study, it is aimed to determine the level of compliance of individuals to preventive health behaviours before, during and, after the pandemic in order to interrupt or reduce the spread of the virus in the Covid-19 pandemic. Methods: This study is a descriptive and cross-sectional study. "Demographic Information Form" and "Questionnaire of Health Behaviors Regarding Influenza" were used as data collection tools. The questionnaire form prepared was designed as 16 questions, 5-point Likert type. The questionnaire contains the answers of the participants regarding the 14 rule implementation situations before, during and after the flu. The universe of this study was individuals living in 81 provinces in Turkey between 1-9 April 2020. In this study, snowball-sampling method was used. The data were collected with an online questionnaire Aim: In this study, it is aimed to determine the level of compliance of individuals to preventive health behaviours before, during and, after the pandemic in order to interrupt or reduce the spread of the virus in the Covid-19 pandemic. Methods: This study is a descriptive and cross-sectional study. "Demographic Information Form" and "Questionnaire of Health Behaviors Regarding Influenza" were used as data collection tools. The questionnaire form prepared was designed as 16 questions, 5-point Likert type. The questionnaire contains the answers of the participants regarding the 14 rule implementation situations before, during and after the flu. The universe of this study was individuals living in 81 provinces in Turkey between 1-9 April 2020. In this study, snowball-sampling method was used. The data were collected with an online questionnaire
Keywords: COVID-19 pandemic; Preventive health behavior; Influenza; Descriptive analysis